Contraception for Women with Diabetes Mellitus - Hadisaputra, Wachyu (Indonesian Socety of Obstetrics and Gynecology, 2014)
use in women with diabetes mellitus. Method: Literature review. Result: Women in the reproductive age who are affected by a wide range of chronic medical conditions, one of which is diabetes mellitus (DM), may experience adverse health effects pre-conception and in pregnancy. This condition will influence outcome of pregnancy and contraceptive choice after delivery. Planning the use of contraception for women with DM who would experience high-risk pregnancy is a necessity, and counseling must consider the safety of different types of contraception that in comparison to the risk of pregnancy. WHO has provided a guideline on choosing contraception, which is available from the UK Medical Eligibility Criteria for Contraceptive Use (UKMEC), as the basis for contraception selection for women with DM. For DM patients without complication any type of contraception can be used in consideration for the advantages and disadvantages of each type of contraception. For diabetics with complications or multiple risk factors, in the selection of contraceptive, hormonal contraception (especially for combined hormonal contraception (CHC) pill and injection method) requires proper consideration and consultation with health care providers. [Indones J Obstet Gynecol 2014; 4: 226-231] Keywords: complications, contraception, diabetes mellitus, hormonal, pregnancy